SOMALI PIRATES TAKE TO THE HIGH SEAS: EXPEDIENCY OR LONG-TERM PIRATE STRATEGY? - Fouche, Henri (Scientia Militaria - South African Journal of Military Studies, 2011)
In 2008 the highest number of attacks recorded against ships in the world was reported to have taken place off the coast of Africa. These attacks were carried out at greater distances from land, along the east coast of Africa, than ever before. In this article the extent of piracy and armed robbery against ships in the African context and underlying causes of piracy and armed robbery against ships off the coast of East Africa will be presented. The objective is to analyse incidents and the land and sea based causes in East Africa to account for the shift in strategy from attacking ships in territorial waters to attacking ships on the high seas. A secondary aim is to determine, in view of the shifting background to the attacks, the responsibilities of navies and other role players in the process of countering such attacks. The article suggests that states need to review national legislation related to maritime security and that all state role players in the maritime domain need to cooperate more efficiently.